An overview of Education in the Caribbean and implications for the Chief Education Officer - Craig, Dennis R. (My University, 1993)
This paper attempts to examine some salient characteristics of education in the English-speaking Caribbean. It outlines the situation with respect to primary, post-primary and secondary education, technical and vocational education and training, and teacher education. It is concluded that world pressures on the Caribbean make it imperative for the pace of educational development to be accelerated. The Chief Education Officers and their professional staff are seen as the means of ensuring that this happens.
Keywords: Primary education